Experience with deflazacort in children and adolescents after renal transplantation - Schärer, Karl; Feneberg, Reinhard; Klaus, Günter; Paschen, Christian Felix; Wüster, Christian; Mehls, Otto; Schaefer, Franz (Pediatric nephrology, 2000)
Deflazacort (DFZ) has been proposed as an alternative drug for immunosuppression after renal transplantation (TX), with fewer side effects than conventional glucocorticoids. We investigated renal function, body growth, body fat, and bone mineral density (BMD) after switching from oral methylprednisolone (MPR) to equivalent doses of DFZ 1-9 years after TX in 20 patients aged 5-20 years, selected because of severe adverse effects from previous steroid therapy. At conversion the patients received a mean dose of 7.4±2.4 mg DFZ/m2 per day. The drug was continued for a mean of 3.7 (1.2-5.5) years. Under DFZ, the glomerular filtration rate dropped slightly (NS). A single rejection episode occurred. Growth velocity significantly improved in the 1st year on DFZ treatment and height standard deviation score (SDS) increased steadily after introduction of DFZ (from -2.64 to -1.96 after 4 years, P=0.06). However, in 10 prepubertal children the height gain (+0.20 SDS in 2 years on DFZ) was not significant and the overall mean annual growth rate after TX was similar to that in 10 matched prepubertal TX children on continued MPR treatment. Relative obesity, estimated from mean body mass index corrected for height, was reduced from +1.11 SDS at the start of DFZ to +0.71 SDS after 2 years (P=0.03) and to +0.39 SDS after 4 years (NS). BMD-SDS of the lumbar spine (L2-4) increased after 1 year on DFZ (P=0.005). In conclusion, DFZ is well tolerated and safe in pediatric patients after TX. It improves relative obesity and bone mineralization. However, body growth is not significantly influenced pre puberty.
Gesehen am 11.01.2021